2020
DOI: 10.37411/pedagogika.v11i2.172
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Komunikasi Kepala Sekolah dalam Meningkatkan Kinerja Guru

Abstract: Tujuan penelitian ini adalah untuk mengeksplorasi dan mendeskripsikan strategi komunikasi kepala sekolah dalam meningkatkan kinerja guru, jenis-jenis komunikasi yang di terapkan kepala sekolah dalam meningkatkan kinerja guru, apa saja hambatan komunikasi kepala dalam meningkatkan kinerja guru dan bagaimana upaya yang dilakukan kepala sekolah dalam mengatasi hamabatan komunikasi. Penelitian ini merupakan penelitian kualitatif yang dilaksanakan di SMP IT Ash- Shiddiqi Kecamatan Pemayung.Data dikumpulkan de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…This is in accordance with previous study which found that school principal communication to improve teacher professionalism was through oral (direct calls and warnings) and written (warning letters) to convey information to teachers, and principal communication in improving teacher discipline was by arriving on time and giving late examples. and for students (A. R. Djailani, 2015;Suriansyah & Aslamiah, 2015). Finally, to go home, the principal's communication about increasing teacher responsibility is to communicate between individuals and find solutions with the school committee and supervisors and related education offices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with previous study which found that school principal communication to improve teacher professionalism was through oral (direct calls and warnings) and written (warning letters) to convey information to teachers, and principal communication in improving teacher discipline was by arriving on time and giving late examples. and for students (A. R. Djailani, 2015;Suriansyah & Aslamiah, 2015). Finally, to go home, the principal's communication about increasing teacher responsibility is to communicate between individuals and find solutions with the school committee and supervisors and related education offices.…”
Section: Discussionmentioning
confidence: 99%
“…School principal communication to improve teacher professionalism is through verbal (direct calls and warnings) and written (warning letters) to convey information to teachers, and principal communication in improving teacher discipline is to come on time and provide role models for students. Finally, to go home, the principal's communication about increasing teacher responsibility is to communicate between individuals and find solutions with the school committee and supervisors and related education offices (A. R. Djailani, 2015). The more effective interpersonal communication, organizational culture, job satisfaction and achievement motivation and achievement motivation, the higher the interpersonal communication of teachers in High School (SMA) Humbang Hasundutan Regency.…”
Section: Discussionmentioning
confidence: 99%
“…Transparasi atau keterbukaan merupakan salah satu unsur yang sangat penting dalam menciptakan suasana yang harmonis dalam suatu organisasi. (Ulfa & Fitria, 2021) Dalam lembaga pendidikan tranparasi menjadi salah satu factor utama berjalannya suatu kegiatan sesuai dengan tujuan. Untuk itu kami sebagai kepala sekolah sangat terbuka kepada semua guru mulai dari semua kegiatan pembelajaran beserta kegiatan extrakurikuler sekolah yang tentu membutuhkan banyak dana pengeluaran yang bernominal banyak dari yayasan.…”
Section: Tranparasiunclassified
“…Sedangkan strategi keputusan dan tindakan mendasar yang di buat oleh manajemen puncak dan di implementasikam oleh jumlah jajaran dalam suatu organisasi dalam rangka mencapai tujuan organisai tersebut. (Aqliyah, 2020). Jadi dapat di artikan bahwa strategi adalah sebuah ide yang dilaksanakan untuk mencapai tujuan dengan memerhatikan penyesuaian antara sumber daya organisasi dengan peluang dan tantangan.…”
Section: Hasilunclassified